Optimization of 99mTc-MAA SPECT/CT Imaging for 90Y Radioembolization Using a 3D-Printed Phantom - Sara Ungania; Marco D’Arienzo; Sandro Nocentini; Marco D’Andrea; Vicente Bruzzaniti; Raffaella Marconi; Emilio Mezzenga; Bartolomeo Cassano; Erminia Infusino; Antonino Guerrisi; Antonella Soriani; Lidia Strigari (Applied Sciences, 2022)
Radioembolization (RE) with 90Y-microspheres has gained widespread acceptance as a safe and effective technique for treating liver malignancies. Accurate quantification in RE is a key step in treatment planning optimization and is becoming a pressing issue in light of the Directive 2013/59/EURATOM. The aim of this study was to develop a SPECT/CT imaging protocol for quantitative imaging optimization in RE based on cutting edge imaging technology (Symbia IntevoTM system provided with the innovative xSPECT software) and a novel anthropomorphic 3D-printed phantom. In the present study, 99mTc-labeled macroaggregated albumin was used as a surrogate radiopharmaceutical for treatment planning. Gamma camera calibration factors and recovery coefficients were determined performing preliminary SPECT/CT acquisitions of a point source, a cylindrical homogeneous phantom and the NEMA/IEC phantom. Data reconstruction was performed using the built-in xSPECT package, using both the Ordered Subset Expectation–Maximization (OSEM) and the Ordered Subset Conjugated Gradient (OSCG) algorithm. Specific regions of interest (ROIs) were drawn on the MIM 6.1.7 system according to the physical volume. The quantification procedure was validated using the anthropomorphic phantom provided with a fillable liver section and spheres of different diameters (20 mm, 40 mm and a 40 mm spherical shell). The measured activity concentration in all geometries is consistent within 4%, demonstrating that the xSPECT software permit an absolute quantification in anthropomorphic geometry largely within the 10% recommended from the manufacturer. Caution is advised in the presence of spherical objects with a necrotic core, as underestimations in the order of 20% were obtained.